Online condolences given to relatives of deceased non-public figures. Reconnaissance research - Kulak, Ilona (Papers in Linguistics, 2025)
The article is the first part in a series to be published on online comments posted by users on social media under other users’ posts about the death of their loved ones who were not public figures. It aims to introduce the topic of condolence posts – a relatively new and not fully researched phenomenon. The material was excerpted from Facebook (from the profiles of people living in south-western Lesser Poland). The article outlines the state of research on linguistic funeral rituals, with particular emphasis on studies of texts from Internet portals. It also discusses proposals for using the methodological achievements of pragmalinguistics, sociolinguistics, ethnolinguistics and axiolinguistics to analyse the collected utterances. Types of sui generis Internet obituaries that trigger an avalanche of comments are also presented. Furthermore, the elements of Internet condolence messages, perceived as speech acts related to politeness taking a written form, are indicated, i.e. condolence (sympathy), consolation (comfort), an expression of the sender’s feelings, a positive reference to the deceased and/or their life, a message addressed to the deceased, a prayer. The article also offers a brief overview of visual and linguistic means used by Internet users.